IMPACT OF THE REACTIVATION ON THE POPULAR COOPERATION SYSTEM ON PEASANT AND NATIVE COMMUNITIES - Roel Alva, Luis Andres (2024)
Peasant and native communities have been at a disadvantage in their development expectations due to deficiencies in sectors such as infrastructure and health, which demonstrates the need for public policies focused on allowing access to basic services and the exercise of the fundamental rights of each individual belonging to these communities. In seeking to deepen this, the general objective is to propose a regulatory proposal aimed at reactivating the National System of Popular Cooperation, reoriented to the development of peasant and native communities. The research used primary sources, stories such as interviews with former officials of the second government of Fernando Belaúnde Terry, in order to collect information on the methodology and implementation of the National Popular Cooperation System; and secondary, collecting information regarding the creation, implementation, development and achievements of the National Popular Cooperation System, amounts allocated for public investment, as well as the emblematic works executed, concluding …that the figure of Popular Cooperation not only seeks to fulfill the constitutional duty of continuing with the decentralization process of the country, but also seeks the creation of a better and more structured decentralization in the territorial areas where our peasant and rural communities are located. natives, offering an ideal environment for greater social, economic, and cultural development. It is also worth emphasizing the importance of materializing this public policy through a standard of legal normative hierarchy, since this would establish responsibilities for various sectors and entities of the Executive Branch (President of the Republic and his Council of Ministers) requiring modification of the Organic Laws of the Executive Branch, of Regional Governments and Municipalities, as well as the Organization and Functions Laws of the Ministries involved, among others.